PROFOUND OF KOBZAR’S POETRY - Пушик, С. Г. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the author highlights the poet’s mythological world, gives numerous parallels in his works, illustrates similarity of poetic meter of the written works and kolomyiky-cuckoos, remarks that the collection «Rusalka Dnistrovaya», which Taras Shevchenko read, expresses the thought that the mermaid, engraved by craftsman Danylo Ekoliuk on the beam of his own house in the village of Biloberezka over Cheremosh, is connected with the publication of «Rusalka Dnistrovaya» and Great Kobzar’s ancestor – Ivan Boyko was the prototype of the hero of the story «Varnak».